Distance Difference Test for Detection of Malicious User in Cognitive Radio - Rajput, Seema; Chaudhari, Amol; Landge, Pratiksha; Kumbhar, Swapnali (Asian Journal of Electrical Sciences, 2012)
A number of wireless applications have been growing over the last decade. Most of the frequency spectrum has already been licensed by government agencies, such as Federal Communications Commission (FCC). Therefore, there exists an apparent spectrum scarcity for new wireless applications and services. Cognitive radio(CR) can efficiently utilize the unused spectrum for secondary usage without interfering a primary licensed user. In cooperative environment, a primary licensed user can share spectrum occupancy information with a secondary user to enable dynamic spectrum access. However, a secondary user needs to verify accuracy of the spectrum occupancy information and it comes from the legitimate primary users. Without the verification, a malicious user can falsify the spectrum occupancy information. This can result in Interference to the primary users and Primary User Emulation attack(PUE) which can minimize spectrum occupancy for secondary user. In this paper, we propose to develop an efficient technique to verify the source of the spectrum occupancy information to be from the legitimate primary user thereby maximizing the spectrum utilization efficiency and minimizing any interference to the primary licensed users.